The effect of body composition value in 12-14 aged teenagers' physical fitness - Oksay Oguz; A. Gursel Oguz (Selcuk University, 2016)
In this study of the effect of body composition value on 12-14 aged teenagers' physical fitness; testing and evaluation of height, weight and body composition of different age groups are shown separated. According to evaluation of children' physical fitness; there is a remarkable difference between the height of the group doing sports and the one do not. There is no big difference of evaluation between the same groups of children. Also, there is a big difference of height and body fat percentage results between two groups. Between groups of age 12 and 13 doing sports; there are differences of height and weight however; there is no difference of body fat percentage. Between group of age 12 and 13 not doing sports; there is a significant difference of height and weight, however; there is no difference of body fat percentage. Between group of age 13 and 14 doing sports; there is no difference of any values except height and weight. Between group of age 12-14 doing sports there are remarkable differences of height, weight and body fat percentage. However there is no difference between the one who are not doing sports. Physical fitness test results are similar to other studies and other country norms.